IMPROVING LISTENING ABILITY THROUGH ENGLISH SONGS - Ribut Sabartono (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2016)
This present study was aimed at investigating how to increase listening skill using English songs, and how to motivate the student in learning listening. The background of this study was commenced by the important framework concept in using English songs in the interaction process of communication in the classroom. The research used classroom action research. The respondent consists of20 students at the eighth grade of SMP Achmad Yani Puger in the academic year of 2016-2017. In the data gathering process, the researcher used listening cloze test administered in both cycle I and cycle II.The data analysis  of listening ability using English songs using description score, and statistics to see the average of the students score after the first observation have been done, the students score 81,35. It can be concluded that listening teaching process through English songs can increase the students’ listening ability. Key words: students’ listening ability, English songs